Paroxysmal sympathetic hyperactivity in brain damage (scientific review). Part 1 - O.V. Kravets; V.A. Sedinkin; V.V. Yekhalov; Yu.O. Ploshchenko; O.O. Zozulya (Медицина неотложных состояний)
Paroxysmal sympathetic hyperactivity (PSH) is a separate form of fever of central origin and is a neurological syndrome characterized by simultaneous paroxysmal occurrence of hypertension, hyperpyrexia, tachycardia, tachypnea, increased sweating and dystonic posture due to sympathetic activation in brain damage. PSH is a syndrome that can manifest itself in a wide range of clinical symptoms. Paroxysmal sympathetic hyperacti-vity is an example of a clinical correlate of central and autonomic nervous system dysfunction. Almost all cases of PSH are associated with craniocerebral trauma, hypoxia, and acute cerebrovascular accident. There is a disengagement theory and a model of the excitation-inhibition relationship of the PSH pathogenesis. In 2014, an expert consensus group proposed a PSH-assessment measure (PSH-AM), which can not only serve as a reliable diagnostic criterion but also stratify the severity of PSH. Assuming clinical evaluation as the current gold standard, PSH-AM has a sensiti- vity of 94 % when used retrospectively. In the treatment of patients with traumatic brain injury, PSH-AM can help avoid misdiagnosis, increase diagnostic efficiency, save time, and reduce economic costs. Hypodiagnosis of PSH can lead to an increase in mortality, disability, length of hospital stay and material costs, but timely diagnosis will allow optimizing treatment for PSH.